2019
DOI: 10.1103/physrevb.99.041117
|View full text |Cite|
|
Sign up to set email alerts
|

Flat energy bands within antiphase and twin boundaries and at open edges in topological materials

Abstract: A model for two-dimensional electronic, photonic, and mechanical metamaterial systems is presented, which has flat one-dimensional zero-mode energy bands and stable localized states of a topological origin confined within twin boundaries, antiphase boundaries, and at open edges. Topological origins of these flat bands are analyzed for an electronic system as a specific example, using a two-dimensional extension of the Su-Schrieffer-Heeger Hamiltonian with alternating shift of the chains. It is demonstrated tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 50 publications
7
19
0
Order By: Relevance
“…where k 1 = k ⋅ a 1 and k 2 = k ⋅ a 2 are dimensionless lattice momenta. In good agreement with the ZPA results [18], the energy bands are calculated as fully gapped at (e, d x , d y ) = (1 3, 0, 1 3) and (e, d x , d y ) = (−1 3, 1 3, 0). Topological phase diagrams -Topological phase diagrams in d-space are calculated using the inversionsymmetry indicators (ν 0 ; ν 1 ,ν 2 ).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…where k 1 = k ⋅ a 1 and k 2 = k ⋅ a 2 are dimensionless lattice momenta. In good agreement with the ZPA results [18], the energy bands are calculated as fully gapped at (e, d x , d y ) = (1 3, 0, 1 3) and (e, d x , d y ) = (−1 3, 1 3, 0). Topological phase diagrams -Topological phase diagrams in d-space are calculated using the inversionsymmetry indicators (ν 0 ; ν 1 ,ν 2 ).…”
supporting
confidence: 85%
“…and 1D flat-band DW states -We argue that the ZPA 1D boundary modes are a physical manifestation of the DPs that wind the BZ. ZPA have shown that the DWs of the 2D SSH chain host the one-dimensional flat bands [18], which we reproduce in Fig. 4.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…This results in locally metallic filaments in a semiconducting host. In fact, the TB can be considered a 2D Dirac metal with flat electronic bands of edge states [39]. WOx provides an excellent example of quasi-periodic patterns of shear planes [40,41], and intriguingly, in a certain x regime, it is also a high-temperature superconductor, with the superconductivity probably strongest on the shear planes-recall the comments on possible filamentary superconductivity above, since dopant (polaronic) charges will preferentially decorate shear planes (and TBs).…”
Section: Elasticity and Short-long-range Competitionsmentioning
confidence: 99%
“…One of the two topological gapped phases, hosting mid-gap MZMs, occurs at |µ| < 2|ω| and ∆ > 0 and the other at |µ| < 2|ω| and ∆ < 0, while nontopological gapped phases arise at |µ| > 2|ω|. Mechanical systems of magnetically coupled spinners [43][44][45][46] have recently been used to simulate a number of electronic tight-binding Hamiltonians. The spinner ladder system pictured in Fig.…”
mentioning
confidence: 99%